Behavior in public places : notes on the social organization of gatherings - Goffman, Erving (New York : The Free Press, 1966)
Erving Goffman effectively extends his argument in favor of a diagnosis of deviant behavior which takes account of the whole social situation.
Bibliografija i bilješke uz tekst
Keywords: etnometodologija; društvena interakcija; ponašanje